Articulated Motion and Deformable Objects 7th International Conference, AMDO 2012, Port d$1 (BAndratx, Mallorca, Spain, July 11-13, 2012. Proceedings /s - Perales, Francisco J.; Fisher, Robert B.; Moeslund, Thomas B.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 7th International Conference on Articulated Motion and Deformable Objects, AMDO 2012, held in Port d'Andratx, Mallorca, Spain, in July 2012. The 27 papers presented were carefully reviewed and selected from 44 submissions. The volume also contains one full paper length invited talk. The conference dealt with the following topics: advanced computer graphics (human modeling and animation); human motion (analysis, tracking, 3D reconstruction and recognition); multimodal user interaction and applications; and affective interfaces (recognition and interpretation of emotions, ECAs -- embodied conversational agents in HCI).
Keywords: Computer science; Artificial intelligence; Computer graphics; Computer vision; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Image Processing and Computer Vision; Pattern Recognition; Computer Graphics; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).